CO2-based poly (propylene carbonate) with various carbonate linkage content for reactive hot-melt polyurethane adhesives. (January 2020) - Liu, Zenghe; Huang, Jiqing; Chen, Shuo; Huang, Yan; Ding, Fengxia; Guo, Weiqiang; Lei, Dong; Yang, Lei; Qing, Feng-Ling; You, Zhengwei
Abstract: Reactive hot-melt polyurethane adhesives (RHMPA) are compelling green adhesives without any solvent. However, current RHMPAs are mainly made from non-renewable petroleum-based polyols. Poly (propylene carbonate) (PPC) derived from abundant, cheap and renewable greenhouse gas CO2 is a high-profile green renewable polyol. Here, a series of RHMPAs (PPC-RHMPAs) based on PPC with different carbonate linkage content were prepared. The difference of carbonate linkage content of PPC-RHMPAs was investigated by 1 H NMR and FTIR. The effects of carbonate linkage content on the moisture-curing rate, crystallization behavior, thermal stability, mechanical properties and adhesion properties of the resulted PPC-RHMPAs were analyzed and discussed by real-time FTIR, DSC, TGA, tensile and adhesion tests. This work would pave a way for designing high-performance PPC-RHMPAs.